KEPEMIMPINAN KEPENDIDIKAN DALAM MENINGKATKAN KUALITAS PENDIDIKAN DI SEKOLAH MENENGAH ATAS BRAWIJAYA SMART SCHOOL - Achmad Yoni Prasetyo; Maskuri Maskuri; Dwi Fitri Wiyono (VICRATINA, 2022)
A leader is important in achieving the success and goals of an organization, just as a leader has an important role in achieving educational and learning goals. In leading, the leader must show professionalism to achieve educational goals, so the leader must play the role of planning, monitoring, etc. Improving the quality of education is one of the goals to be achieved, so in order to improve the quality of education, the director himself must be able to motivate and guide teachers towards professional work to improve the quality of education. In addition, leaders must be able to solve various problems at school. think analytically and conceptually and should always strive to be a teacher mediate in solving various problems faced by workers subordinates, and trying to make decisions satisfactory for all. This study aims to determine the role of pedagogical leadership in improving the quality of education in SMA Brawijaya Smart School Malang. The research method used is qualitative research with data collection techniques in the form of direct interviews with resource persons related to the director of SMA BSS Malang. The results of the study show that a leader who prioritizes Disciplined, courteous and democratic leaders have a role to play It is very important to improve the quality of education, this is of course responsibilities and obligations of a leader in achieving quality